2015
DOI: 10.1007/s13349-015-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

A field study on distributed fiber optic deformation monitoring of overlying strata during coal mining

Abstract: In this paper, the distributed optical fiber sensing technology based on Brillouin optical time-domain reflectometer (BOTDR) was employed to monitor and analyze the force and deformation of the overlying rock strata during the coal mining process in Huaibei, China. The selection and arrangement of the sensing cables were introduced, together with details on data collection and analysis. Four types of sensing cables were vertically installed into a borehole to monitor the strata deformation. The monitoring data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Regarding the different types of used cables, it was concluded that PSC was unable to monitor land subsidence at deep levels due to its small stiffness. Another borehole strata deformation monitoring with BOTDR-based sensors is also reported in [ 108 ].…”
Section: Civil Engineering Shm Applications With Dofsmentioning
confidence: 99%
“…Regarding the different types of used cables, it was concluded that PSC was unable to monitor land subsidence at deep levels due to its small stiffness. Another borehole strata deformation monitoring with BOTDR-based sensors is also reported in [ 108 ].…”
Section: Civil Engineering Shm Applications With Dofsmentioning
confidence: 99%
“…where T 0 and ε 0 is the initial temperature and strain, respectively, ν B (0) is the initial BFS, C T and C ε are the temperature and strain coefficient of BFS, respectively (approximately 1.1 MHz/ • C and 0.05 MHz/µε [40]). With the BOTDR, a pulsed light is launched into one end of a single-mode optical fiber, and the Brillouin backscattered light generated by it is observed using a heterodyne receiver at the same end.…”
Section: Botdrmentioning
confidence: 99%
“…Although many others using DOFS to monitor the movement of overlying strata or overburden caused by underground coal mining. The main result and intention of these tests are mainly the height of water conducting fracture zone caused by overburden movement [37][38][39][40] rather than the dynamic evaluation process of strata movement.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al proposed a displacement monitoring methodology of rock layers overlying a coal seam in Zhu Xian-zhuang mine (China) based on fiber Bragg grating displacement sensors [8]. Cheng et al measured the deformation of overlying rock layers of a coal seam by employing a BOTDR-based monitoring method [9]. Wang and Luan built a fiber mesh structure on mine roof and conducted BOTDR strain measurement [10].…”
Section: Introductionmentioning
confidence: 99%